High performance framework (Queensland Academy of Sport, 2012)
The purpose of this framework is to outline aspects such as the role and responsibilities of the Queensland Academy of Sport (QAS), structure and management within the QAS plus the components necessary to ensure that programs operate at a high performance level. The document is to assist in the understanding of the QAS`s: • Organisation • Funding and Management • High Performance Programs It is anticipated that this framework could be used as a guide primarily to current and potential stakeholders to assist: • Management staff of the QAS • Program Leaders (normally referred to as the Head Coach) and Service Team Members • External Organisations. The purpose of the Queensland Academy of Sport is targeted at: 1. Queensland Athletes representing in Australian Senior Teams. 2. Queensland Athletes achieving world class performances in international competition. 3. The QAS being the knowledge and resource hub for the development of elite athletes in Queensland. Another general role of the QAS is to augment the performance and development of the high performance sports system in Queensland. The structure of the QAS includes two High Performance Teams overseen by High Performance Directors. Each team consists of a group of Primary, Partnership and possibly Individual Programs. In addition, the Service Divisions of Sport Science (SS), Sports Medicine (SM), Strength and Conditioning (S&C) and Athlete, Career and Education (ACE) have been imbedded in one of the teams. • Sport Science and Sports Medicine are in Team 1. • Strength and Conditioning and ACE are in Team 2.